(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article provides a comparative analysis of verb formation in English and Uzbek languages. Verbs are a crucial part of any language, serving as the backbone of communication and expression. Understanding the mechanisms of verb formation in different languages helps in language acquisition, translation, and effective communication.